The INFLUENCE OF ECONOMIC GROWTH, EDUCATION, AND ACCESS TO SANITATION ON THE PREVALENCE OF STUNTING IN HORSESHOE, EAST JAVA: PENGARUH PERTUMBUHAN EKONOMI, PENDIDIKAN, AKSES SANITASI TERHADAP PREVALANSI STUNTING DI TAPAL KUDA, JAWA TIMUR - Puspaningtyas, Noffitria; Fathorrazi, Moehammad; Komariyah, Siti (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The research aims to examine the effect of economic growth, education, and sanitation access on stunting prevalence in the Tapal Kuda region using a dynamic econometric approach, specifically the System Generalized Method of Moments (SYS-GMM). The data utilized in this study were sourced from Central Bureau of Statistics and the Ministry of Health for the period 2019–2023. The results indicate that stunting is persistent, meaning that the prevalence of stunting in the previous year significantly affects the following year. Economic growth does not have a significant impact on reducing stunting prevalence, suggesting that an increase in GDP per capita has not directly improved children's nutritional status. Meanwhile, education shows a positive correlation with stunting prevalence, indicating that regions with higher education levels tend to have better awareness and accuracy in reporting stunting cases. Conversely, sanitation access has a negative and significant effect on stunting, demonstrating that improved sanitation can be a key factor in reducing stunting prevalence. These findings highlight the importance of policies focused on improving sanitation access, nutrition education programs, and targeted nutrition interventions to accelerate the reduction of stunting rates in the Tapal Kuda region. Keywords : Stunting, Economic Growth, Education, Sanitation, SYS-GMM, Tapal Kuda